2014
DOI: 10.4236/jss.2014.29019
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Information Needs of Elderly People: A Survey in Chinese Rural Community

Abstract: A survey about the information needs of elderly people could find out the information required to address the needs of the aged in a community. Analyzing data collected from 600 elderly people through field investigation with a questionnaire in a rural community in central China, the results show that the preferred information format of the majority of aged people is audio and/or visual information product, especially audio product. Most of the aged people stated that they were in need of healthy and medical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…First, senior users mainly focus on physiological and somatic health information. This is consistent with previous studies in China, the UK and Germany (Zou and Zhou, 2014;Robinson and Robertson, 2014;Theis et al, 2019). However, seniors in Germany were more interested in the diagnosis and treatment of diseases, whereas our study showed that seniors in China paid more attention to daily health self-management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, senior users mainly focus on physiological and somatic health information. This is consistent with previous studies in China, the UK and Germany (Zou and Zhou, 2014;Robinson and Robertson, 2014;Theis et al, 2019). However, seniors in Germany were more interested in the diagnosis and treatment of diseases, whereas our study showed that seniors in China paid more attention to daily health self-management.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies investigated the health information needs of seniors. A survey on these needs in rural China showed that seniors needed physiological health information the most (Zou and Zhou, 2014). A group interview in China emphasized the seniors' need for mental health information (Shi and Luo, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%